Air Medical Transport of Cardiac Patients in Nova Scotia - Kaarsberg, Sue; Goldstein, Judah; Tallon, John M. (DALHOUSIE MEDICAL JOURNAL, 2003)
Objective: To perform a descriptive program review of the air medical transport (AMT) of cardiac patients within Nova Scotia's air medical transport program. Methods: A retrospective study of patients with primary, non-traumatic cardiac conditions transported by the provincial air ambulance program between August 1, 1997 and August 31, 1998, who are 16 years of age or older (non-pediatric). Various aspects were examined, including diagnosis, geography of transport, medications given by the air medical crew (AMC) and by sending institution, complications of transport and interventions performed by the AMC as well as total time spent at the sending institution by the AMC. Data was extracted from the flight patient care records (PCR) with full preservation of patient confidentiality. Results: The AMT program transported a total of 240 patients during the study period. Of these a total of 155 patients (64.6%) were 16 years of age or older. Of that total, 46 had a primary cardiac diagnosis (29.7%): 34 were male (73.9%) and 12 were female (26.1%). The mean age of these transported patients was 62.4+/-10.0 ears and 59.1+/-17.6 years for males and females respectively. Most cardiac patients were diagnosed with a myocardial infarction (22 patients, 47.8%), with the remaining patients diagnosed with unstable angina, peri-cardiac arrest, congestive heart failure (CHF) or primary arrhythmia. Only 12 of the patients diagnosed with myocardial infarction (MI) had previously been treated with thrombolytics (54.5%). Heparin and intravenous nitroglycerine were the medications most commonly maintained by the AMC, while morphine, midazolam, nitroglycerine and dimenhydrinate were common medications given by the AMC. Twenty-three patients experienced some form of in-flight complication or change in condition, with brady- arrhythmias being the most common (23.9%). Nine patients were intobated by the referring hospital or by the AMC prior to departure and maintained as such throughout the flight. The average amount of time spent at the referring hospital packaging each patient was 64.07 minutes. Conclusions: This paper describes the demographics of the cardiac population utilising air medical transport in Nova Scotia. Cardiac patients comprise a large proportion of the total patient cohort in the AMT program (almost one-third) in the adult population transported. Recognition of this fact, in conjunction with review of provincial, tertiary-care, cardiac transfer policies has led to the development of specific cardiac AMT indications for Nova Scotia.